Replenishing and Recycling an Exhausted History in Lydia R. Diamond's Voyeurs de Venus. Issue 3 (3rd July 2019) - Ghasemi, Mehdi
Summary: In this article, I offer an analysis of Lydia R. Diamond's Voyeurs de Venus and argue that the replenishment of Saartjie Baartman's hilstory by Diamond can provide alternative perspectives to that exhausted piece of hilstory. In my analysis, I explore the ways that Diamond uses to flashlight the dark and unknown areas in the life of this historical figure. I demonstrate how the repetition and revision of that hilstory links the present to the past and helps the playwright to make a comparison between the status of black women at different eras and areas. Since the play draws upon a strong feminist potential to interrogate the intersectional concerns of race, sex, class and gender, I also approach the play from the standpoints of intersectionality. I argue that the intersections of race, sex, class and gender have five outcomes or "Penta Ps, " namely the promotion of white male scientists and white race, the privilege of whiteness, the perversion of the black female body, culture and race, the profit of white masters, and the pleasure of white male spectators and owners.